Pendampingan Penguasaan Mufradat Melalui Ice Breaking Tebak Makna dalam Pengajaran Bahasa Arab di MDTA Madinatul Ulum Desa Margaluyu - Munir, Dede Rizal Munir; Ningsih, Hanu Nuantia; Fajar, Ahmad (Humanism : Jurnal Pengabdian Masyarakat, 2024)
For a student, increasing Arabic vocabulary is very important, especially for those who are involved in Arabic language education. The fewer vocabulary a student has, the slimmer his chances of mastering the context of Arabic sentences. Therefore, to make the learning process more interesting, media is needed in the learning process that is easy to understand and easy for students to master. So that the learning process can achieve the desired goals and be more dynamic, other tools or media are needed, such as audio-visual media, print projectors, films, games and so on. The opportunity to master the Arabic learning of vocabulary more easily if the learning media is better. The Arabic Language Education Study Program's Community Service uses the Participatory Action Research (PAR) method, namely a research method carried out in a participatory manner among MDTA Madinatul Ulum Margaluyu students. The service team will try to provide training and mentoring as a stimulus in an effort to improve students' abilities in mastering Arabic vocabulary through Picture Card Media.The results of the Arabic Language Education Study Program Service Team succeeded in improving the abilities of MDTA Madinatul Ulum City Margaluyu students regarding mastery of Arabic vocabulary at MDTA Madinatul Ulum Margaluyu.